Assessment of Inhibin B as a Biomarker of Testicular Injury Following Administration of Carbendazim, Cetrorelix, or 1, 2‐Dibromo‐3‐Chloropropane in Wistar Han Rats. (30th January 2013) - Moffit, Jeffrey S.; Her, Leah S.; Mineo, Anthony M.; Knight, Brian L.; Phillips, Jonathan A.; Thibodeau, Michael S.
<x xml:space="preserve">Abstract</x> Although histopathology is considered the gold standard for assessing testicular toxicity in the nonclinical setting, identification of noninvasive biomarkers for testicular injury are desirable to improve safety monitoring capabilities for clinical trials. Inhibin B has been investigated as a noninvasive biomarker for testicular toxicity. This study investigates the correlation of Inhibin B in Wistar Han rats with the onset and reversibility of testicular histopathology from classical testicular toxicants carbendazim, cetrorelix acetate (CTX), and 1, 2‐dibromo‐3‐chloropropane (DBCP). The dose regimen included Interim (day 8), Drug (day 29), and nondosing Recovery (day 58) Phases. Inhibin B was not effective at predicting the onset of carbendazim‐ or CTX‐mediated testicular pathology in rats. Inhibin B was reduced by DBCP administration at the end of the Drug Phase only, acting as a leading indicator of the onset of testicular toxicity before the onset of germ cell depletion. However, since Inhibin B was only decreased at the end of the Dosing Phase and not at the Recovery Phase, when the onset of testicular pathology occurred, it is unclear if monitoring Inhibin B would provide sufficient advanced warning for the onset of testicular pathology. Furthermore, follicle stimulating hormone was decreased following CTX and DBCP administration in the Interim Phase and CTX in the Drug Phase. Inhibin B has limited predictive capacity as a leading testicular biomarker in rats.